DAMPAK KEGIATAN MANUSIA TERHADAP KERAGAMAN DAN POLA DISTRIBUSI KUMBANG SUNGUT PANJANG (COLEOPTERA: CERAMBYCIDAE) DI GUNUNG SALAK, JAWA BARAT - Noerdjito, Woro Anggraitonongsih (JURNAL BIOLOGI INDONESIA, 2012)
The impact of human activities on the Longhorn Bettles Diversity and Their Distribution Patterns in Mount Salak, West Java, had been conducted by observation and collecting efforts on various types of habitats which include undisturbed and disturbed forests. Longhornbeetles are one of the largest groups of wood borers and therefore typical forest dependent insects. The species diversity and distribution pattern of these beetles may vary with speciescomposition age of the trees, and stability of the forest, and therefore they are a useful bioindicator for assessing forest condition. The beetles were collected using ?Artocarpus branchtraps?, a bait trap. It is a bundle of about 5-6 freshly-cut branches of Artocarpus heterophyllus (jackfruit), about 80 cm long with many leaves, tied up and hung from a tree trunk or standingpoles at 1.5 m above the ground. The trap attracted longhorn beetles that need feeding for reproductive maturity. Ten traps were set at each study site (habitat). The attracted beetleswere collected every week by beating method, because in West Java forest area, beetles are usually gathered by the 6th day after trap setting. Light traps were also set up for 2 night, at each habitat for collecting nocturnal longhorn beetles. Totally 578 specimens were collected, consisted 38 species of longhorn beetles, dominated by small body size species less than 10mm. Out of these 38 species, some species were known distributed in certain habitat andelevation, other species have wider distribution, where as some species were endemic and new record for Java.Keywords: distribution, diversity, longhorn beetles, Mount Salak